Shape of Evasive Prey Can Be an Important Cue That Triggers Learning in Avian Predators - Linke, Daniel; Elias, Marianne; Klečková, Irena; Mappes, Johanna; Matos-Maraví, Pável (Frontiers in Ecology and Evolution, 2022)
Abstract Advertising escape ability could reduce predatory attacks. However, the effectiveness of certain phenotypic cues (e.g., colour, shape, size) in signalling evasiveness are still unknown. Understanding the role of such signals in driving predator learning is important to infer the evolutionary mechanisms leading to convergent evasiveness signals among prey species (i.e., evasive mimicry). We aim to understand the role of colour pattern (white patches on dark background) and morphology (extended hindwings) in driving learning and avoidance of escaping prey by surrogate avian predators, the European blue tit. These cues are common in butterflies and have been suspected to advertise escape ability in nature. We use dummy butterflies harbouring shape and colour patterns commonly found in Skippers (family Hesperiidae). The prey models displayed the studied phenotypical cues (hindwing tails and white bands) in factorial combinations and we tested whether those cues were learned as evasive signals and generalised to different phenotypes. Our results suggest that hindwing tails and white bands can be associated with prey evasiveness and that wild blue tits might learn and avoid attacking prey models bearing such phenotypic cues Wild blue tits seem to have an initial preference for the study phenotype consisting of white patches and hindwing tails. Nonetheless, such an initial preference was substantially reduced once this prey phenotype was associated with escaping ability. This suggests that the same morphological cues might be interchangeable as preference/avoidance signals. Further investigation of the salience of hindwing tails vs white bands as cues for escaping ability, revealed that predators can associate both colour pattern and shape to difficulty of capture, and possibly generalise their aversion to other prey harbouring those cues. More studies with larger sample sizes are needed to confirm this trend. Altogether, our results highlight the hitherto overlooked role of shape (butterfly hindwing tails) for signalling prey unprofitability.